ANALYSIS OF REASONS, CIRCUMSTANCES AND CONSEQUENCES OF MANUFACTURING TRAUMATISM DURING PRODUCTION OF MAIN PHARMACEUTICAL PRODUCTS AND PHARMACEUTICAL PREPARATIONS - Сирик, Алина; Евтушенко, Ольга; Зомчак, Виктория (SWorldJournal, 2020)
. In the article there is analyzed statistics on the causes, consequences and circumstances of occupational injuries at the pharmaceutical products and pharmaceuticals for the period from 2013 to 2018, and is found that organizational factors lead to 80%